Efeito da calagem no desenvolvimento da Pitaia Amarela (Hylocereus megalanthus) cultivada em vaso - Evangelista, Francisco Lopes (2022)
Correction of soil acidity has as main objective to establish the balance between acidic and basic cations in the soil so that plants can develop properly. In this sense, there are studies indicating the need for liming for some fruit trees, in the case of pitaya, this type of study is still insufficient. Thus, the effect of increasing doses of lime on the growth and nutrition of yellow pitaya was evaluated. The experiment was carried out partly in a greenhouse, partly in open air. Vases with a capacity of 25 L, filled with a Dystrophic Yellow Argisol (V = 35%) were used. The treatments were distributed in a randomized block design, with five treatments and four replications. Limestone doses were: 0; 0.48; 0.96; 1.44 and 1.92 t ha-1. The soil Fertilization was carried out with urea, simple superphosphate, potassium chloride and FTE BR12. The liming promoted an increase in the concentrations of Ca and Mg in the soil, increased the pH, the sum of bases, the base saturation, while causing a reduction in the potential acidity. The dose of 1.92 t ha-1 promoted the highest values of pH(6.6), SB(38.8), V(82.9%) and resulted in the greatest reduction of H+Al (8 mmolc dm-3), also reducing acidity exchangeable. Liming did not influence growth parameters (number of cladodes, number of areolas, length of cladodes, diameter and thickness of cladodes) at 180, 270 and 360 days. At 360 days there was influence of liming on the absolute growth rate of the number of decladodes, the dose of 1.92 t ha-1 resulted in the highest value. Liming did not influence the analyzed chlorophyll fluorescence parameters. The nutritional contents were satisfactory for growth in the first year of cultivation. The dose of 1.92 t ha-1 promoted the highest contents of Ca, while the doses of 0.44 and 1.92 t ha-1 promoted contents considered satisfactory for Fe.